Inter-analyst variability in swimming competition analysis - Hudson, C. (Procedia Engineering, 2014)
This paper quantified the inter-analyst variability in the time at which a swimmer reached a certain distance in a race, which is a key measure in swimming competition analysis. Prior to this paper coaches had assumed that differences in these times were solely due to changes in the swimmer's performance. This assumption was tested by asking four trained and experienced British Swimming analysts to calculate the time at which a swimmer reached four distances in ten randomly selected 100 m races. The inter-analyst variability was found to be between 0.02 s and 0.34 s.